An experimental study: various influence factors affecting interfacial shear performance of UHPC-NSC. (10th March 2020) - Zhang, Yang; Zhang, Chongyang; Zhu, Yanping; Cao, Junhui; Shao, Xudong
Highlights: The shear properties of UHPC-NSC interface were systematically studied through a series of double-sided direct shear tests. Different factors affecting the shear capacity of the UHPC-NSC interface were discussed. The factors included strength of NSC, ages of UHPC at loading, curing regimes for UHPC, surface treatment of NSC substrate, wettability of NSC substrate, addition of expansive agent for UHPC, and exertion of tensile or compressive stress on the interface except for shear stress. Abstract: Ultra-high performance concrete (UHPC) is an innovative cement-based material with high tensile and compressive strengths, extremely low permeability, and excellent durability. It is suitable for repair and rehabilitation of damaged normal strength concrete (NSC) structures. However, in order to ensure that the UHPC layer co-works well with the NSC structures, a good shear bond between UHPC and NSC is the main concern. In this study, the shear properties of UHPC-NSC interface were systematically studied through a series of double-sided direct shear tests, and the shear capacity and corresponding interfacial failure modes were obtained. Different factors affecting the shear capacity of the UHPC-NSC interface were discussed, namely, strength of NSC, age of UHPC at loading, curing regime for UHPC, surface treatment of NSC substrate, wettability of NSC substrate, addition of expansive agent for UHPC, and exertion of tensile or compressive stress on the interface except for shear stress. The test results showed that the interface between the UHPC layer and NSC substrate exhibited an excellent bond behavior. Most specimens failed in a mode of partial interface failure + partial NSC failure or complete NSC failure in shear, and the remaining few specimens developed purely interface failure. Also, shear failure of some test specimens performed a certain degree of brittleness. According to the test results, the higher the strength or wettability of NSC substrate, the greater the shear capacity of the interface. The shear capacity of UHPC-NSC interface increased rapidly when the age of UHPC increased from 3 days to 7 days, and at the age of 7 days, the shear strength of UHPC-NSC interface could reach more than 90% of the final shear strength. It was revealed that the shear strength of UHPC-NSC interface with steam curing for UHPC at a temperature of 90 °C reduced by 12.9% compared to that with normal curing. The addition of expansive agent to UHPC slowed down the development of the shear capacity of UHPC-NSC interface at the early age and slightly reduced the shear capacity at the age of 28 days and 180 days. Roughing NSC surfaces could significantly improve the interfacial shear capacity. Moreover, the number and area of UHPC tenons in the holes, UHPC grooved joints or post-installed rebars could also affect the shear capacity of the interface. The shear capacity of UHPC-NSC interface under combined tensile and shear stresses decreased significantly, while the shear capacity under combined compressive and shear stresses increased obviously with the increment of shear capacity gradually decreased as the increase of normal compressive stress.